1984
DOI: 10.1172/jci111381
|View full text |Cite
|
Sign up to set email alerts
|

Effective and fibrin-specific clot lysis by a zymogen precursor form of urokinase (pro-urokinase). A study in vitro and in two animal species.

Abstract: Abstract. A single-chain 55,000-mol wt form of urokinase (UK), similar to that previously isolated from urine, was purified from a transformed kidney cell culture medium and characterized; and its fibrinolytic properties were evaluated. The preparation immunoprecipitated with UK antiserum, had a low intrinsic amidolytic activity that was 0.1% of its active derivative, and resisted diisopropyl fluorophosphate treatment and inactivation by plasma inhibitors. The single-chain UK was therefore designated pro-UK. In Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
117
0
2

Year Published

1986
1986
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 322 publications
(120 citation statements)
references
References 24 publications
1
117
0
2
Order By: Relevance
“…We resolved the paradox of PA remaining active in cells pretreated with DFP by showing that PA was stored in these cells in a pro-enzyme, single-chain form (Table 111). Pro-UK does not have detectable amidolytic activity when assayed with a specific, chromogenic substrate (14,22,24). It can be converted to an active form through catalytic activity of plasmin (14) .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We resolved the paradox of PA remaining active in cells pretreated with DFP by showing that PA was stored in these cells in a pro-enzyme, single-chain form (Table 111). Pro-UK does not have detectable amidolytic activity when assayed with a specific, chromogenic substrate (14,22,24). It can be converted to an active form through catalytic activity of plasmin (14) .…”
Section: Resultsmentioning
confidence: 99%
“…Since PA is a serine protease, and therefore should be inhibited by DFP, this finding may seem paradoxical . However, our results (Table 111) showed that PA was present in these cells in the form of an amidolytically inactive proenzyme that could not bind DFP (14,22,24) and consequently was protected from inactivation by this compound .…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…Binding to its GPI-anchored receptor (uPAR, CD87) on the cell surface, uPA activates plasminogen to plasmin which, in turn, degrades extracellular matrix proteins (1,2). The established role of uPA in breast cancer is to proteolytically cleave the extracellular matrix (3).…”
Section: Introductionmentioning
confidence: 99%
“…Fibrin dissolution is also regulated by inhibitors of PLG activation, such as PLG activator inhibitor-1 (PAI-1), which is a major inhibitor of uPA and tPA in vivo and is produced by many cell types upon exposure to TGF-β, TNF-α and other cytokines [10,11]. Cells synthesize uPA as a single-chain precursor form (pro-uPA or scuPA) that can be converted to the two-chain uPA (tcuPA) after cleavage at Lys158-Ile159 by plasmin [8] or other activators [12]. Thrombin cleaves scuPA at Arg156-Phe157, two residues preceding the activation cleavage site, to generate a less active form of tcuPA called thrombincleaved tcuPA (uPAt) [13] The mechanism by which these two amino acid residues prevent conversion of zymogen scuPA into proteolytically active tcuPA is not known.…”
mentioning
confidence: 99%